Pre- and intraoperative cerebral near-infrared spectroscopy and postoperative delirium: Results of a prospective cross-sectional trial. Issue 44 (4th November 2022) - Fischer-Kumbruch, Moritz; Jung, Carolin; Hinken, Lukas; Trübenbach, Dominik; Fielbrand, Rieke; Schenk, Isabel; Diegmann, Oliver; Krauß, Terence; Scheinichen, Dirk; Schultz, Barbara
Abstract : Postoperative delirium (PODE) is a serious complication that can occur during the first few days after surgery. A number of causes can make delirium more likely; one factor to consider is hypoxia during anesthesia. In this study, the pre- and intraoperative cerebral regional oxygen saturation (rSO2 ) as measured by near-infrared spectroscopy (NIRS) was to be examined with regard to an association with the occurrence of PODE in patients undergoing major abdominal procedures. Data from 80 patients (33 women, 47 men) was examined. The mean age was 66.31 ± 10.55 years (between 42 and 84 years). Thirteen patients developed PODE. The preoperative rSO2 values ( P = .10) and the rSO2 values during the steady state of anesthesia ( P = .06) tended to be lower in the delirium group than in the non-delirium group. There was a significant correlation between the preoperative rSO2 and the preoperative hemoglobin values ( P < .001). The variance of rSO2 during the steady state of anesthesia was significantly greater in the delirium group compared to the non-delirium group ( P = .03). In two patients from the delirium group, rSO2 dropped below 50%; they also had a minimum mean arterial pressure below 50 mm Hg, which could have disturbed cerebral autoregulation. The duration of rSO2 decreases (>10%, >15%, >20%) and increases (>10%) compared to the preoperative values was not significantly different between patients with and without PODE. The results suggest that NIRS could be a useful monitoring method for patients undergoing abdominal surgical procedures, on the one hand to recognize patients with low pre- or intraoperative rSO2 values, and on the other hand to detect changes in rSO2 values during anesthesia.